ANEMPIRICAL INTERROGATIONOF INSTITUTIONAL NORMS AND PATTERNS IN UNDERGRADUATE RESEARCH - Samuel C. Avemaria Utulu (European Scientific Journal, ESJ, 2013)
The study evolved through an empirical observation of how undergraduate research is practiced at the Redeemer’ University (Redeemer’s), Nigeria. The institutionalization process framework advanced by Farashahi, Hafsi and Molz (2005) was then used to empirically interrogate how actors that are involved in undergraduate research through various taken-for-granted actions play out the processes of institutionalizing undergraduate research norms and pattern in the Redeemer’s. The study is a longitudinal and an interpretive study that adopted the traditional ethnography research methodology which informed its triangulation of three data collection techniques namely, ethnographic observation, interview and questionnaire. The data collection techniques generated qualitative and descriptive statistical data that was used to observe the institutionalization of undergraduate research process (that is, research administration at the College and Departmental levels, research objective setting and research topic selection approaches at the students level) at three stages-externalization, objectivation and internalization. The finding shows that there are evolving institutionalization of undergraduate research norms and patterns at the Redeemer’s. Recommendations were provided on the reasons why the emerging institutionalization of undergraduate research norms and patterns need to be formalized and adopted as source of knowledge for regulating research at the Redeemer’s.